Managing pediatric psoriasis: update on treatments and challenges—a review - A. A. Hebert; J. Browning; P. C. Kwong; A. M. Duarte; H. N. Price; E. Siegfried (Journal of Dermatological Treatment)
Background Psoriasis is a chronic, immune-mediated inflammatory disease with prominent cutaneous features, although the limited number of medications approved for pediatric psoriasis makes treating this population difficult. This review provides an overview of the challenges associated with diagnosing and treating pediatric psoriasis as well as the approved and off-label treatments for children and infants with psoriasis.Methods Articles relevant to pediatric psoriasis were identified using a series of PubMed searches. Topics relevant to pediatric psoriasis were explored, including disease characteristics, epidemiology, treatment efficacy and safety, and access to care. Publications previously known to the authors were also included.Results Clinical features of psoriasis can be challenging to identify clinically, and patients face challenges gaining access to treatment. Most medications that have been approved for adult psoriasis lack data and labeling to support safe and effective use in pediatric patients, and therefore access is limited. A growing number of clinical trials using biologic agents for pediatric psoriasis aim to broaden available treatment options but may also raise unique concerns associated with the use of these medications in children.Conclusion Pediatric psoriasis is underrecognized and often undertreated. Clinicians must balance relative risks and potential benefits when developing a treatment strategy for these patients.